Sagot :
Answer:
Given the functions f(x)=x+3 and g(x)=2x+3.Fⅈnd (f ∙ g)(x
Step-by-step explanation:
Given f (x) = 3x + 2 and g(x) = 4 – 5x, find (f + g)(x), (f – g)(x), (f × g)(x), and (f / g)(x).
To find the answers, all I have to do is apply the operations (plus, minus, times, and divide) that they tell me to, in the order that they tell me to.
(f + g)(x) = f (x) + g(x)
= [3x + 2] + [4 – 5x]
= 3x + 2 + 4 – 5x
= 3x – 5x + 2 + 4
= –2x + 6
(f – g)(x) = f (x) – g(x)
= [3x + 2] – [4 – 5x]
= 3x + 2 – 4 + 5x
= 3x + 5x + 2 – 4
= 8x – 2
(f × g)(x) = [f (x)][g(x)]
= (3x + 2)(4 – 5x)
= 12x + 8 – 15x2 – 10x
= –15x2 + 2x + 8
F F(x)
- (X) = - - -- ---
G G(x)
3x + 2
= -----------
4 - 5x
Sana naintindihan mo OwO
Jiyaa(。・∀・)ノ゙
Answer:
(f - 9) (x) = x-1
Step-by-step explanation: